2017
DOI: 10.1007/978-94-024-1079-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Recovery of Learning Deficits Induced by Developmental Pb2+ Exposure

Abstract: Lead (Pb) is a historically well-documented environmental neurotoxin that produces developmental cognitive learning and memory impairments. These early neurodevelopmental impairments cause increased brain excitability via disruption of Ca mediated signaling during critical periods of synaptogenesis inducing competition with I through NMDAs resulting in altered brain development and functioning across the lifespan. Interestingly, Pb has been shown to decrease GABA transport and uptake, decrease spontaneous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Furthermore, this early postnatal time-period is contemporaneous with the GABA-shift in the first 3postnatal weeks of the rat's life (Ben-Ari, 2012;Ben-Ari et al, 2006) and the developmental pattern of the genes that regulate that GABA-shift have been shown to be altered by Pbexposure (Neuwirth et al, 2018;Neuwirth, 2014). These observations are consistent with reports that suggest developmental Pb-exposure may disrupt early neurodevelopmental excitation-inhibition balancing mechanisms that may lead to persistent life-long disruptions in inhibitory regulatory mechanisms that contribute to proper frontoexecutive and learning functions (Neuwirth et al, 2018;Neuwirth et al, 2017;Neuwirth, 2014). These observations suggest that the rat's ASST behavioral performance may rely more heavily upon sensory function than what is currently discussed in both the neurotoxicology and the developmental behavioral neuroscience literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, this early postnatal time-period is contemporaneous with the GABA-shift in the first 3postnatal weeks of the rat's life (Ben-Ari, 2012;Ben-Ari et al, 2006) and the developmental pattern of the genes that regulate that GABA-shift have been shown to be altered by Pbexposure (Neuwirth et al, 2018;Neuwirth, 2014). These observations are consistent with reports that suggest developmental Pb-exposure may disrupt early neurodevelopmental excitation-inhibition balancing mechanisms that may lead to persistent life-long disruptions in inhibitory regulatory mechanisms that contribute to proper frontoexecutive and learning functions (Neuwirth et al, 2018;Neuwirth et al, 2017;Neuwirth, 2014). These observations suggest that the rat's ASST behavioral performance may rely more heavily upon sensory function than what is currently discussed in both the neurotoxicology and the developmental behavioral neuroscience literature.…”
Section: Discussionsupporting
confidence: 91%
“…Since developmental Pb-exposure has been shown to disrupt the development of the GABAergic system (Neuwirth et al, 2018;Neuwirth, 2014) resulting in aberrations in behavioral inhibitory control (Neuwirth et al, 2017), the current findings suggest the possibility that similar GABAergic reductions in inhibitory frontoexecutive functioning may be influencing learning and decision making processes assessed in the ASST. More work in this area is needed to understand the extent to which sex-specific dysexecutive functions related to GABAergic and non-GABAergic-mediated mechanisms may be involved in response to developmental Pb-exposure.…”
Section: Discussionmentioning
confidence: 71%
“…The PFC and the HP were selected since the HP has been the brain region specifically studied in association with the GABA-shift in neurodevelopment [ 11 , 12 ] and less is known regarding the PFC. Further, within the brain the PFC, HP and the cerebellum are most vulnerable for lead-induced brain damage as each region accumulates more lead deposition than other brain regions in clinical studies of children [ 36 ]. Thus, since less the PFC and its relationship with the HP are vulnerable to Pb 2+ exposure during critical stages of neurodevelopment and they regulate higher order cognitive processes regarding frontoexecutive functions in contrast to the cerebellum, the study revealed that perinatal lead exposure could alter the expression of mRNA from genes involved in the GABA-shift.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that each brain region may “shift” at distinct time-periods of development and may equally present with neurotoxicant susceptibilities resulting in developmental neuropathologies during these precise time-periods. As such, Pb 2+ exposure competes with critical Ca 2 + − dependent gene activity dysregulating the GABA-shift as a model of neurological disease [ 34 , 36 ] consistent with reports by Khale et al [ 21 ], and Hyde et al [ 35 ].,Moreover, neurodevelopmental Pb 2+ exposure in children lacks an early developmental behavioral signature, yet interestingly neurocognitive patterns of impairments can be assessed later in life under behavioral learning and memory conditions [ 34 , 36 ]. Further, it has been shown that NMDA R blockade by Pb 2+ and MK-801 can directly impair the acquisition learning [ 37 , 38 ], but MK-801 antagonism has also been shown to impede the expression of inhibitory learning across the lifespan [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted here that more research is needed to understand whether such evidence-based therapies not only reduce circulating BLLs, but also more importantly, ameliorate brain lead deposition [46,[60][61][62]. Consistently, new costeffective therapies as dietary taurine intake in addressing lead induced neurodevelopmental problems across the lifespan are currently being explored in animal models [63][64][65], but require a concerted effort in confirming its efficacy through clinical studies.…”
Section: Recommendations: a Public Health Perspectivementioning
confidence: 99%